Exploring Secondary Students' Writing of Recount Text Based on Appraisal System Through Web Blog - Rina Rismayanti; Yogi Setia Samsi; Totoh Tauhidin Abbas (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to focus on attitudes as a sub of appraisal system. The purpose of the study is to find out what types of Attitude are most commonly found in students’ writing Recount text through Web-blog and the students’ responses in writing recount text through web blog. This research uses a qualitative method, with the descriptive case study as the research design. This research was conducted in the eighth grade of senior high school in Karawang. The researcher uses observation, Interview and documentation to collect data. 6 learners participated in writing Recount text and interview. The learners' writing are conducted from web blog. The study results found that the student's recount writings, it was found to affect 17, judgment 6 and appreciation 6. Then, based on the results of interview data that has been conducted on students, it can be concluded that the use of web blogs as a medium for writing recount text can be responded well and positively by students.